PI4K2A deficiency causes innate error in intracellular trafficking with developmental and epileptic‐dyskinetic encephalopathy. Issue 9 (25th July 2022) - Dafsari, Hormos Salimi; Pemberton, Joshua G.; Ferrer, Elizabeth A.; Yammine, Tony; Farra, Chantal; Mohammadi, Mohammad Hasan; Ghayoor Karimiani, Ehsan; Hashemi, Narges; Souaid, Mirna; Sabbagh, Sandra; Najarzadeh Torbati, Paria; Khan, Suliman; et al.
Abstract: Objective: Intracellular signaling networks rely on proper membrane organization to control an array of cellular processes such as metabolism, proliferation, apoptosis, and macroautophagy in eukaryotic cells and organisms. Phosphatidylinositol 4‐phosphate (PI4P) emerged as an essential regulatory lipid within organelle membranes that defines their lipid composition and signaling properties. PI4P is generated by four distinct phosphatidylinositol 4‐kinases (PI4K) in mammalian cells: PI4KA, PI4KB, PI4K2A, PI4K2B. Animal models and human genetic studies suggest vital roles of PI4K enzymes in development and function of various organs, including the nervous system. Bi‐allelic variants in PI4KA were recently associated with neurodevelopmental disorders (NDD), brain malformations, leukodystrophy, primary immunodeficiency, and inflammatory bowel disease. Here, we describe patients from two unrelated consanguineous families with PI4K2A deficiency and functionally explored the pathogenic mechanism. Methods: Two patients with PI4K2A deficiency were identified by exome sequencing, presenting with developmental and epileptic‐dyskinetic encephalopathy. Neuroimaging showed corpus callosum dysgenesis, diffuse white matter volume loss, and hypoplastic vermis. In addition to NDD, we observed recurrent infections and death at toddler age. We further explored identified variants with cellular assays. Results: This clinical presentation overlaps with what was previously reported in two affected siblings with homozygous nonsense PI4K2A variant. Cellular studies analyzing these human variants confirmed their deleterious effect on PI4K2A activity and, together with the central role of PI4K2A in Rab7‐associated vesicular trafficking, establish a link between late endosome‐lysosome defects and NDD. Interpretation: Our study establishes the genotype–phenotype spectrum of PI4K‐associated NDD and highlights several commonalities with other innate errors of intracellular trafficking.